PEMODELAN ENERGI BARU TERBARUKAN (EBT) MELALUI PENDEKATAN DINAMIS UNTUK KETAHANAN ENERGI KABUPATEN SUMBAWA 2017-2027 - Aryanto, Nova; Jaya, Ahmad; Hudaya, Chairul (Jurnal TAMBORA, 2020)
In an effort to increase the value of the Electrification Ratio value reaches 99.9% andUtilization of New and Renewable Energy (EBT) of up to 25% by 2025 is requiredThe General Plan for National Energy (RUEN) which is revealed to be the General DraftRegional Energy (RUED). Sumbawa as an area in West Nusa Tenggarahas the potential for EBT in the form of Solar Energy Potential, Hydro Energy, and Thermal EnergyEarth and Sea Energy require strategic policies to manage andmeet the energy security of the region. This study aims to predictEnergy needs, and mapping the potential of EBT, in order to obtain a mixenergy (energy mix) is balanced. This research was conducted using toolssoftware Long-range Energy Alternatives Planning System (LEAP) withdynamic systems approach. Data obtained from PT. PLN UP3 Sumbawa, RUPTL DataPLN NTB Region, Bapedda Kab. Sumbawa and Data from BPS Kab. Sumbawa. ResultThis research shows that the potential of EBT can be integrated in RUED formeet the energy needs of the region. Therefore, this research canproduce accurate energy demand forecast for Sumbawa Regencyin particular the use of regional green energy sources (Green Energy) to achieve thisenergy security for the great and dignified Sumbawa Regencyencouraging the formation of RUED Sumbawa Regency in line with the Indicator StrategySDGs program launched by the Government, both the Central Government andLocal Government especially the Clean Energy (Green Energy) program.